ЭТИОЛОГИЧЕСКАЯ СТРУКТУРА ВОСПАЛИТЕЛЬНЫХ ЗАБОЛЕВАНИЙ КОНЪЮНКТИВАЛЬНОЙ ПОЛОСТИ В Г. КАРАГАНДА (Experimental biology, 2015)
It is shown that the microflora of conjunctival cavity of eyes, basically presented as coagula negative (62,5 %) and coagula positive (20,58 %) staphylococcus.
Keywords: microflora of conjunctival; staphylococcu